SELF-ESTIMATES OF ABILITY TO TEACH SCIENCE. - Groff, Patrick J. (Science Education, 1962)
The article presents a study in which elementary school teachers themselves rate their ability to teach science at the end of a four-year college program that included subject-matter preparation, science methodology, and student teaching. 645 student teachers from six different California colleges participated in this study. The study was conducted when they were just completing the last of their education methods courses and their student teaching. The subject of science was ranked fifth by these 645 student teachers, among the eleven subjects given to them. The women who comprised approximately 85 per cent of the total study group, also assigned fifth ranking to science, while the men in the study ranked it third. Science got 24.2 per cent fewer points than reading, the first-ranked subject of women, and 12.8 per cent more points than their eleventh-ranked subject, physical education. Social studies was assigned top priority by the men but gave it only 5.1 per cent more points than science. The study concludes that the pre-service teachers considered themselves relatively better-prepared for the teaching of science.